Improving the Conditions for the Provision of Tax Benefits in the Framework of Consuming Relations on State Support of Capital Investments - P. S. Alpatov (Теоретическая и прикладная юриспруденция)
This article discusses the application of newly introduced investment benefits to investment projects for the implementation of capital investments that began and (or) ended to the appropriate change in the legislation. As a significant direction in the development of the state tax policy in the field of stimulating capital investments, the need for a balanced approach is indicated in the resolution of this issue. So, the application of a less favorable previous law should not overcome subsequent norms that provide the best position for the taxpayer. At the same time, unlimited records of past investments for new benefits should also not be allowed.